ABCC8-Related Maturity-Onset Diabetes of the Young (MODY12): Clinical Features and Treatment Perspective. Issue 3 (September 2016) - Ovsyannikova, Alla; Rymar, Oksana; Shakhtshneider, Elena; Klimontov, Vadim; Koroleva, Elena; Myakina, Natalya; Voevoda, Mikhail
Abstract Maturity-onset diabetes of the young (MODY) is a heterogeneous group of diseases associated with gene mutations leading to dysfunction of pancreatic β-cells. Thirteen identified MODY variants differ from each other by the clinical course and treatment requirement. Currently, MODY subtypes 1–5 are best-studied, descriptions of the other forms are sporadic. This article reports a MODY12 clinical case, caused by a mutation in the gene of the ATP-binding cassette transporter sub-family C member 8 (ABCC8 ), encoding sulfonylurea receptor 1. Diabetes manifested in a 27-year-old non-obese man with epilepsy in anamnesis. No evidence of ketosis was present, pancreatic antibodies were undetectable, and C-peptide remained within the reference range. During the initial investigation, non-proliferative diabetic retinopathy and elevated albumin excretion rate was revealed. After 4 months, diabetes was complicated by pre-proliferative retinopathy and diabetic macular edema. Recurrent hypoglycemia and an increase in body weight was observed on moderate and even small insulin doses. Taking into account the clinical features and the presence of diabetes in four generations on the maternal side, screening for all MODY subtypes was performed. A mutation in theABCC8 gene was found in proband and in his mother. After the insulin discontinuation, gliclazide modified release combined with sodium/glucose cotransporter 2 (SGLT2) inhibitors was started. This treatment eliminated hypoglycemia and improved glycemic variability parameters. A decrease in the amplitude of glucose excursions was documented by continuous glucose monitoring. After 3 months of treatment, glycemic control was still optimal, and no hypoglycemic episodes were observed. The case report demonstrates the clinical features ofABCC8 -associated MODY and the therapeutic potential of a combination of sulfonylurea with SGLT2 inhibitor in this disease.